Oxygen-enriched defect type iron-copper-aluminum nano flower-shaped catalyst for efficiently and synergistically degrading NO and methylbenzene and preparation method thereof

The oxygen-deficient iron-copper-aluminum nanoflower-shaped catalyst was prepared by the double-titration anion intercalation method, which solved the problems of insufficient oxygen vacancy when the existing catalysts were synergistically degraded NO and toluene, and achieved efficient and low-cost catalytic effect.

CN119633823APending Publication Date: 2025-03-18XIANGTAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411762126.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

When existing catalysts synergistically degrade NO and toluene, there are problems such as insufficient oxygen vacancy, small specific surface area, high cost, low selectivity, and easy to cause secondary pollution and high energy consumption.

Method used

The double-titration anion intercalation method is used to uniformly precipitate the iron-copper-aluminum trimetals in situ in one step to form an oxygen-rich iron-copper-aluminum nanoflower-like catalyst, which improves the ion exchange capacity and structural topological transformation of the material, and increases oxygen vacancies and active sites.

Benefits of technology

The ability to efficiently synergistically degrade NO and toluene is achieved, reducing costs, avoiding secondary pollution, and improving the stability and toxicity of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633823A_ABST
    Figure CN119633823A_ABST
Patent Text Reader

Abstract

The invention discloses an oxygen-enriched defect type iron-copper-aluminum nano flower-shaped catalyst for efficiently and synergistically degrading NO and methylbenzene and a preparation method of the oxygen-enriched defect type iron-copper-aluminum nano flower-shaped catalyst. The catalyst is characterized in that CuO and Al2O3 are doped into Fe3O4 through a one-step in-situ synthesis method, the catalyst is prepared through a double-titration anion intercalation method, FeSO4. 7H2O, Cu (NO3) 2.3 H2O and Al (NO3) 3.9 H2O serve as metal sources, Fe3O4 accounts for 55%-65% of the total mass of the catalyst, and the doping amount of CuO is 25%-30%, and the doping amount of Al2O3 is 10%-15%. The prepared catalyst is of a nanoflower-ball-shaped mesoporous structure, has a large specific surface area and rich oxygen vacancies and active sites, not only has excellent performance of synergistically degrading NO and toluene at medium and low temperatures, but also has stable sulfur and water resistance, is green, safe, environment-friendly and low in energy consumption, and has a wide industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0003] The invention relates to the technical field of environmental catalysis, and in particular to an oxygen-rich defective iron-copper-aluminum nano-flower-shaped catalyst for efficiently and synergistically degrading NO and toluene and a preparation method thereof. Background Art

[0005] NO emissions from industrial furnaces and mobile sources x Volatile organic compounds (VOCs) are important common precursors of PM2.5 and ozone, which not only harm biological health, but also cause various climate problems such as photochemical haze and smog, and damage the earth's ecological environment. Toluene is a typical volatile organic pollutant and often appears with NO in industrial production. The selective catalytic reduction of NO using ammonia, which has been widely used in industry, can be used to reduce NO to 2.5% of the total NO. x (NH3-SCR) technology is one of the most energy-saving, environmentally friendly, safe and ideal methods to collaboratively remove organic matter such as toluene. The key to this technology lies in the design of the catalyst.

[0006] The synergistic and efficient removal of NO and toluene requires extremely high catalyst performance. The vanadium, tungsten and titanium-based catalysts currently used in coal-fired power plants have problems such as biological toxicity, high energy consumption, low product selectivity, and poor synergistic performance. Carbon-based catalysts are suitable for low-temperature denitrification, but problems such as carbon loss and high-temperature combustion limit their application in the field of catalytic combustion and purification of VOCs. Manganese-cerium-based catalysts have been studied by some scholars due to their active valence change, but due to their defects such as insufficient active oxygen and few acid sites, there is still competition between NH3, NO and toluene and their intermediates when synergistically polluted, which limits the application of this type of catalyst. Metallic iron, copper and aluminum have been widely studied and applied in various fields due to their excellent medium and low temperature catalytic ability, abundant storage capacity, and green and non-toxic characteristics. However, iron, copper and aluminum metal oxides prepared by traditional co-precipitation or impregnation methods will show obvious mutual inhibition in the synergistic catalytic reduction of NO and oxidation of toluene due to problems such as uneven agglomeration and dispersion, lack of medium and high temperature acid sites, and insufficient active oxygen.

[0007] With the in-depth research in the field of catalysis, the role of oxygen vacancies has gradually been valued. Oxygen vacancies are caused by oxygen defects in the crystal structure. Oxygen vacancy defects can activate oxygen molecules well and provide more active oxygen for catalytic reactions. Nanometal materials are a new type of material. Due to their special atomic arrangement, small-sized nanoparticles of the same element are significantly different from bulk materials. Nanometal materials often bring large specific surface areas and sufficient active sites. However, to date, there have been few reports on oxygen-defect nanometal catalysts for the synergistic degradation of multiple pollutants such as NO and VOC in flue gas. Summary of the invention

[0009] The purpose of the present invention is to provide an oxygen-deficient iron-copper-aluminum nanoflower-shaped catalyst for the efficient synergistic degradation of NO and toluene and a preparation method thereof in view of the problems of insufficient oxygen vacancies, small specific surface area, high cost, low selectivity, easy secondary pollution and high energy consumption in the existing synergistic degradation of NO and toluene catalysts.

[0010] In order to achieve the above object, the present invention adopts the following technical solutions:

[0011] A highly efficient oxygen-defective iron-copper-aluminum nanoflower catalyst for the synergistic degradation of NO and toluene uses a double titration anion intercalation method to uniformly precipitate the three metals of iron, copper, and aluminum in situ in one step, which improves the ion exchange capacity of the material. Structural topological transformation occurs during calcination to form oxygen-rich defect nanoflowers. This morphology allows sufficient contact between the iron, copper, and aluminum metals, which is beneficial to electron transfer and can bring about a large number of oxygen vacancies and active sites, giving it excellent synergistic catalytic degradation of NO and toluene.

[0012] The general formula of the catalyst is FeCuAl-NF, wherein Fe3O4 accounts for 55% to 65% of the total mass of the catalyst, and the doping amounts of CuO and Al2O3 are 25% to 30% and 10% to 15% respectively.

[0013] Furthermore, the nano-flower cluster catalyst has a rich mesoporous structure with a specific surface area of ​​170-200 m 2 / g, total pore volume is 0.2~0.5cm 3 / g, and the average pore size is 3~5nm.

[0014] The preparation method of the oxygen-rich defective iron-copper-aluminum nanoflower catalyst for synergistically degrading NO and toluene comprises the following steps:

[0015] (1) Solution pretreatment: First, prepare iron, copper, and aluminum metal ion solution A, sodium hydroxide solution B, and anion intercalation solution C. Then, place solutions A, B, and C in an ultrasonic bath at 40°C for 10 to 20 minutes to uniformly disperse the ions.

[0016] (2) Generation of catalyst precursor: The double titration anion intercalation method allows the three metals of iron, copper and aluminum to be uniformly precipitated in situ in one step. In the first step, the C solution described in (1) is placed in a magnetic stirring water bath, and then the A and B solutions are slowly dripped into the C solution to control the pH of the solution to be alkaline while controlling the stirring speed. In the second step, the suspension liquid after titration is placed in a vacuum drying oven for aging. In the third step, the precipitate is filtered and the pH is adjusted to neutral with ultrapure water. After suction filtration, the precipitate is immersed in an organic solution, and then suction filtration is placed in a forced air drying oven for drying to generate a precursor.

[0017] (3) Modification of the precursor: Grind the catalyst precursor obtained in step (2) to less than 200 mesh, calcine it in a tubular furnace, and then press it into tablets. The catalyst is sieved into 40-80 mesh.

[0018] In the above method, in step (1), the iron, copper and aluminum metal ion solution is prepared using FeSO4·7H2O, Cu(NO3)2·3H2O and Al(NO3)3·9H2O, and the molar ratio of the three is (2~2.5):(1~1.5):(0.8~1.0).

[0019] In step (1), the concentration of the sodium hydroxide solution is 3.5-4.1 mol / L.

[0020] In step (1), the anion intercalation solution used can be sodium carbonate, sodium nitrate, sodium sulfate, sodium thiosulfate, or sodium dodecyl sulfate solution, and its concentration is 0.35-0.55 mol / L.

[0021] In step (2), the pH of the titration process is controlled at 9.5-10.5, the stirring speed is 260-520 rpm, the titration temperature is controlled at 60-85°C, and the titration speed is 0.05-0.15 mL / s.

[0022] In step (2), the aging temperature is 60-80°C and the aging time is 12-24h.

[0023] In step (2), the organic solvent is one of methanol, ethanol and acetone, the amount of organic solution is 80-180 mL, and the soaking time is 2-3 h.

[0024] In step (2), the drying temperature is 50-70°C and the drying time is 20-25h.

[0025] In step (3), the calcination temperature in the tubular furnace is 350-500°C, the heating rate of the tubular furnace is 5-20°C / min, pure nitrogen is introduced during the calcination process, the nitrogen flow rate is 100-200mL / min, the calcination time is 3.5-5.5h, and the annealing time is 4-7h.

[0026] The present invention will be further described below:

[0027] The oxygen-defective iron-copper-aluminum nanoflower catalyst of the present invention can be used for the catalytic purification of NO and toluene in mobile and fixed source flue gas. The double titration anion intercalation method makes the precipitation between the three metals of iron, copper and aluminum more uniform, which is beneficial to the electron transfer brought about by the interface contact between the metals. During the calcination process, the anions will be partially or completely dispersed, which is beneficial to the dispersion between the metals and is not easy to agglomerate, thereby forming an oxygen-defective iron-copper-aluminum nanoflower catalyst. Due to its special structure, it brings a larger specific surface area, more active oxygen and acid sites, which is beneficial to the synergistic catalytic reaction of multiple pollutants and has immeasurable application prospects in the field of flue gas purification.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The raw materials used in the present invention are rich in content, low in cost, green and pollution-free, can avoid secondary pollution, and alleviate the crisis of non-renewable resources.

[0030] 2. The present invention adopts an in-situ one-step synthesis method catalyst, which has a simple process, strong operability, and is easy for large-scale industrial production.

[0031] 3. The present invention enhances the ion exchange capacity of the catalyst through anion intercalation, strengthens the strong interaction between metal cations and anions, and makes its structure more stable.

[0032] 4. The oxygen-defective iron-copper-aluminum nanoflower catalyst of the present invention contains abundant oxygen vacancies, which are beneficial to the activation of oxygen molecules during the catalytic process, thereby generating more active oxygen and reducing the problem of competition for active oxygen among multiple pollutants.

[0033] 5. The catalyst of the present invention has a nano-flower cluster shape, and the particle size is between 20 and 30 nm, which can expose more active sites. Compared with ordinary metal oxide catalysts, its performance is more efficient, stable and resistant to poison.

[0034] 6. The one-step in-situ doping of copper and aluminum into ferroferric oxide distorts the crystal structure of the catalyst and forms a solid solution, which strengthens the electron transfer between metals and enhances its oxygen migration ability. At the same time, it brings more acidic sites, thereby improving the catalyst's synergistic catalytic degradation of multiple pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a scanning electron microscope image of the oxygen-rich defective iron-copper-aluminum nanoflower catalyst prepared in Example 1.

[0037] Figure 2 This is the pore size distribution diagram of the oxygen-rich defective iron-copper-aluminum nanoflower catalyst prepared in Example 1.

[0038] Figure 3This is the XRD test pattern of the oxygen-rich iron-copper-aluminum nanoflower catalyst prepared in Example 1.

[0039] Figure 4 This is a performance test diagram for the synergistic degradation of NO and toluene by the oxygen-rich defective iron-copper-aluminum nanoflower catalyst prepared in Example 1. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below with reference to specific embodiments, but is not intended to limit the scope of the present invention.

[0042] Example 1

[0043] The preparation method of the oxygen-rich defective iron-copper-aluminum nano-flower-shaped catalyst for synergistically degrading NO and toluene comprises the following steps:

[0044] (1) Add 13.9 g FeSO4·7H2O, 6.04 g Cu(NO3)2·3H2O and 9.38 g Al(NO3)3·9H2O into 100 mL ultrapure water, stir and ultrasonicate at 40°C for 15 min, marked as solution A; dissolve 24 g NaOH in 150 mL ultrapure water, stir and ultrasonicate at 40°C for 15 min, marked as solution B; dissolve 5.3 g Na2CO3 in 100 mL ultrapure water, stir and ultrasonicate at 40°C for 15 min, marked as solution C;

[0045] (2) placing the solution C obtained in step (1) into a magnetic stirring water bath, controlling the temperature to 80°C and the stirring speed to 300 rpm, and then dripping the solutions A and B described in (1) into the solution C at a rate of 0.15 mL / s and 0.10 mL / s, respectively, during which the pH of the solution was controlled to be 9.5-10.5. After the titration, placing the suspension in a vacuum drying oven at 80°C for aging for 24 h;

[0046] (3) filtering the aged suspension obtained in step (2), washing it with ultrapure water, and adjusting the pH value to 6.8. Then, soaking the filtered precipitate in 150 mL of anhydrous ethanol for 2 h, filtering it, and drying it in a 60° C. forced air drying oven for 24 h to obtain a catalyst precursor.

[0047] (4) The catalyst precursor obtained in step (3) was ground into powder, and then placed in a tubular furnace for calcination. The heating rate of the tubular furnace was 10°C / min, and N2 was introduced at a rate of 100 mL / min. The mixture was calcined for 5 h, annealed and cooled for 4.5 h, and then taken out. The powder sample was pressed into tablets and then sieved. The sample with a mesh size of 40-60 was selected as the oxygen-defective iron-copper-aluminum nanoflower catalyst.

[0048] Example 2

[0049] SEM and BET tests of the catalyst of the present invention

[0050] The morphology and surface structure of the catalyst of the present invention were observed by scanning electron microscopy (ZEISS Sigma 300 instrument, Germany). The specific surface area and pore size distribution of the catalyst were characterized by N2 physical adsorption and desorption experiments using a Micromeritics TriStar II 3020 automatic gas adsorption system. After pretreatment of 0.1 g of sample, N2 was used as an adsorbent at a temperature of 77 K. According to the Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halenda (BJH) methods, reasonable specific surface area, total pore volume and average pore size were obtained.

[0051] The results show that the oxygen-defective Fe-Cu-Al nanoflower catalyst is a nanoflower cluster composed of small particles with an average diameter of 20-30 nanometers, with rich mesoporous structure and large specific surface area (171 m 2 / g).

[0052] Example 3

[0053] XRD and EPR tests of the catalyst of the present invention

[0054] The physical structure of the catalyst of the present invention is obtained by a D8 Advance X-ray diffractometer (Cu-Kα radiation, λ=0.15406 nm) produced by Bruker, Germany, in a 2θ range (5°~70°) at a scanning speed of 5° / min. The oxygen vacancies on the catalyst are detected by electron paramagnetic resonance (EPR) (SPINSCAN X, Republic of Belarus). The research results show that the iron-copper-aluminum catalyst of the specific shape contains abundant oxygen vacancies, which can not only improve the activation ability of the catalyst for O2, but also provide active sites for the catalytic reaction, thereby reducing the competition of NH3, NO and toluene for active oxygen and adsorption sites.

[0055] Example 4

[0056] The performance of the oxygen-rich iron-copper-aluminum nanoflower catalyst of the present invention in synergistically degrading NO and toluene was studied.

[0057] The oxygen-defective Fe-Cu-Al nanoflower catalyst prepared in Example 1 of the present invention was used as the experimental object, and 0.6 ml of the catalyst was loaded into a fixed bed quartz reactor for testing. The gas composition was: 500 ppm NO, 500 ppm NH3, 100 ppm toluene, 5.5% O2 and N2 as the balance gas. The total flow rate was 400 mL / min, and the gas hourly space velocity was 40000 h-1 , the reaction temperature is 100~350°C. The test results show that the catalyst has excellent medium and low temperature synergistic degradation of NO and toluene performance, and the NH3-SCR and toluene oxidation reactions promote each other.

Claims

1. An oxygen-rich defective iron-copper-aluminum nanoflower catalyst for efficient synergistic degradation of NO and toluene, characterized in that: CuO and Al2O3 are in-situ doped into Fe3O4, wherein the mass percentages of Fe3O4, CuO and Al2O3 are 55% to 65%, 25% to 30% and 10% to 15%.

2. The oxygen-rich defective iron-copper-aluminum nanoflower catalyst for synergistically degrading NO and toluene according to claim 1, characterized in that: The catalyst morphology is a nano-flower cluster composed of small particles with an average diameter of 20 to 30 nanometers, with a rich mesoporous structure and a large specific surface area of ​​170 to 200 m 2 / g, total pore volume is 0.2~0.5cm 3 / g, and the average pore size is 3 to 5 nm.

3. The method for preparing the oxygen-rich defective iron-copper-aluminum nanoflower-shaped catalyst for synergistically degrading NO and toluene according to any one of claims 1 to 2, characterized in that: The steps include: (1) using a constant temperature ultrasonic method to uniformly disperse anions and cations in a metal salt solution; (2) The precursor of oxygen-defective Fe-Cu-Al nanoflower catalyst was prepared by double titration anion intercalation method; (3) The precursor obtained in (2) is placed in an organic solution for full immersion and activation, and then subjected to a high-temperature structural topological transformation to obtain an oxygen-rich iron-copper-aluminum nanoflower catalyst.

4. The method according to claim 3, characterized in that The solute of the metal salt solution in step (1) includes FeSO4·7H2O, Cu(NO3)2·3H2O, and Al(NO3)3·9H2O, and the molar ratio of the three substances is (2-2.5):(1-1.5):(0.8-1.0). Constant temperature ultrasound refers to ultrasonic treatment at 40°C for 10-20 minutes.

5. The method according to claim 3, characterized in that: The solution used for the intercalation anion in step (2) includes sodium carbonate, sodium nitrate, sodium sulfate, sodium thiosulfate, and sodium dodecyl sulfate solution, and its concentration is 0.35-0.55 mol / L.

6. The method according to claim 3, characterized in that Step (2) is specifically: slowly dripping an iron, copper, and aluminum metal salt solution and a NaOH solution with a concentration of 3.5 to 4.1 mol / L into the anion intercalation solution according to claim 5, wherein the titration rate is 0.05 to 0.15 mL / s, the pH value of the titration process is controlled to 9.5 to 10.5, the stirring rate is 260 to 520 rpm, and the titration temperature is controlled to 60 to 85° C. After the titration is completed, the suspension is coated and placed in a 60 to 80° C. vacuum drying oven for aging for 12 to 24 hours, filtered, and the precipitate pH is adjusted to neutral with ultrapure water. After suction filtration, the precipitate is placed in 80 to 180 mL of an organic solution for immersion activation for 2 to 3 hours, suction filtered again, and placed in a 50 to 70° C. forced air drying oven for drying for 20 to 25 hours to obtain a precursor of an oxygen-rich defective iron, copper, and aluminum nanoflower catalyst.

7. The method according to claim 6, characterized in that The organic solution includes methanol, ethanol and acetone.

8. The method according to claim 3, characterized in that Step (3) is specifically as follows: grinding the precursor obtained in claim 6 into powder, placing it in a tubular furnace at 350-500° C. and calcining it for 3.5-5.5 hours, the heating rate of the tubular furnace is 5-20° C. / min, and pure nitrogen is introduced during the calcination process at a nitrogen flow rate of 100-200 mL / min. After annealing and cooling for 4-7 hours, the precursor is taken out, pressed into tablets, and sieved to obtain a material with a size of 40-80 mesh, thereby obtaining an oxygen-rich, defective, iron-copper-aluminum nanoflower catalyst for the synergistic degradation of NO and toluene.